ANALISIS PINALTI HUKUM MATI KEPADA PERANTARA JUAL BELI NARKOTIKA DAN PEMBELIAN KATEGORI TANAMAN NARKOTIKA (STUDI KASUS NO. 1991/PID.SUS/2019/PN MDN) - Lesson Sihotang; Gelora Butar-butar (Nommensen Journal of Legal Opinion, 2021)
The problem of narcotics at this time has penetrated all elements of the nation, from children to adults, from the lower classes to officials, even law enforcers are not sterile from narcotics abuse. Its abuse is very dangerous to the future of the younger generation and threatens the existence of national security in a nation, so that it requires rules in the form of laws that regulate so as to reduce the number of abuse and distribution of narcotics. especially in Indonesia. The problem in this writing leads to the basis for the judge's consideration in imposing capital punishment on intermediary actors of narcotics sale and purchase group 1 (one) not plants in Decision Number: 1991 / Pid.Sus / 2019 / PN Mdn. Based on the results of the research and discussion carried out by the author in Decision Number: 1991 / Pid.Sus / 2019 / PN Mdn, the basis for the judge's consideration of imposing capital punishment on the intermediary narcotics buying and selling group I non-plant narcotics is based on judges' considerations juridically and non-juridically.considerations, Judicial namely valid evidence in the form of indictment, witness statements, evidence, documentary evidence, statement of the defendant revealed in court. The basis forconsiderations non-juridical consists of background actions, personal conditions, socio-economic conditions.